Circularity Concepts in Forest-based Industries - Food and Agriculture Organization of the United Nations; UNECE; FAO (Geneva: United Nations Publication, 2021)
The study analyses the existing and possible limitations to circular approaches in forest-based industries, namely the woodworking industry (focusing on sawn wood processing, bioenergy production and wood in construction), the furniture industry, the paper and pulp industry as well as industry using cellulose-based fibers and cellulose-based plastics.
Setting the stage for a Circular Forest Sector -- Defining a Circular Economy -- Circularity in Forest-based Industries -- Challenges and Opportunities of circular approaches -- Conclusion and Recommendations
Keywords: Forests products industry; Forests and forestry